Continuing education as a mental health promotion strategy for university professors (Research, Society and Development, 2021)
This research has as its object of study the Permanent Education in Health as a strategy to promote mental health for professors of higher education at a Federal University in the state of Rio de Janeiro. Its general objective is to use Continuing Education with higher education teachers in the development of teaching processes and products as a facilitating strategy for the promotion of mental health. This will be a study with a descriptive and exploratory method, with a quanti-qualitative approach, of a convergent care research type, with application of a semi-structured questionnaire and workshops with Problematization Methodology by the Arch of Maguerez with teachers from the School of Nursing of a Federal University. It is intended to discuss the data obtained in the light of the National Policy for Continuing Education and from the theoretical references of Paulo Freire, National Policy for the Promotion of Health and Positive Mental Health. It is expected that this study will contribute to building tools that enable the promotion of mental health, as well as discussions with professionals about the possible impacts that work can generate on mental health, making them more aware of the need for self-care to improve the quality of life.